Investigating User Perceptions and Usability of Academic Information System Among Public Health Undergraduates in Kuningan - Jona, Kevin Elsy; Sumitra, Irfan Dwiguna (Proceeding of International Conference on Informatics, Engineering, Science & Technology, 2025)
This research is designed to review user perceptions and usability of Academic Information System (SIAKAD) in undergraduate at Public Health Students, Kuningan. The aim is to determine how users perceive the usability of the system (ease, effectiveness and satisfication) and where there can be improvements. We assesed using the User Experience Questionare (UEQ), capturing six standard dimensions and two locally adapted ones: Security and Accessibility. A total of 51 respondents participated in the survey. The results indicated that all standard UEQ dimensions were rated in the "Above Average" category, with Perspicuity and Efficiency being the most notable strengths. Conversely, the Novelty dimension received lower scores, suggesting limited innovation in the system’s design. The other two dimensions of Security and Accessibility performed well above industry standards as users feel more secure with their data and access the system. Overall, the system performed well in pragmatic aspects, particularly clarity and reliability. These outcomes provide useful lessons for future system modifications such as improving interface design, multi-device accessibility, and reinforcing security features